2009
DOI: 10.1068/p6049
|View full text |Cite
|
Sign up to set email alerts
|

Do Pictures of Faces, and Which Ones, Capture Attention in the Inattentional-Blindness Paradigm?

Abstract: Faces and self-referential material (eg one's own name) are more likely to capture attention in the inattentional-blindness (IB) paradigm than other stimuli. This effect is presumably due to the meaning of these stimuli rather than to their familiarity [Mack and Rock, 1998 Inattentional Blindness (Cambridge, MA: MIT Press)]. In previous work, IB has been investigated mostly with schematic stimuli. In the present study, the generalisability of this finding was tested with photographic stimuli. In support of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 33 publications
4
55
1
Order By: Relevance
“…Previous work on inattentional blindness has shown that unexpected objects are more likely to be noticed if they are inherently or currently relevant to the observer (e.g., Calvillo & Jackson, 2014;Devue et al, 2009;Downing et al, 2004;Mack & Rock, 1998;Most et al, 2001). This is in line with a formal model of conscious perception that suggests that sensory input needs to overcome a certain threshold to enter awareness, which can be achieved by means of top-down amplification (Deheane et al, 2006;Ellis, 2001).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous work on inattentional blindness has shown that unexpected objects are more likely to be noticed if they are inherently or currently relevant to the observer (e.g., Calvillo & Jackson, 2014;Devue et al, 2009;Downing et al, 2004;Mack & Rock, 1998;Most et al, 2001). This is in line with a formal model of conscious perception that suggests that sensory input needs to overcome a certain threshold to enter awareness, which can be achieved by means of top-down amplification (Deheane et al, 2006;Ellis, 2001).…”
Section: Discussionsupporting
confidence: 60%
“…It is often assumed that unexpected stimuli are processed on a preconscious level (Mack & Rock, 1998), and some of them succeed in overcoming the threshold of conscious perception due to an additional activating process (often described as "attentional capture"; Calvillo & Jackson, 2014;Devue, Laloyaux, Feyers, Theeuwes, & Brédart, 2009). This amplification is usually caused by the stimuli's current or general relevance, which is, for example, due to the observer's attentional set, the object's evolutionary relevance, its relevance to the observer's self, or its animacy (Calvillo & Jackson, 2014;Devue et al, 2009;Downing, Bray, Rogers, & Childs, 2004;Mack & Rock, 1998;Most et al, 2001;New & German, 2014). However, if an additional activation process causes unexpected objects to reach awareness (Deheane et al, 2006), it seems plausible that the consciousness threshold might be reached by processes other than the relevance-induced attentional capture.…”
mentioning
confidence: 99%
“…Evidence from single-cell recordings (e.g., Perrett, Hietanen, Oram, & Benson, 1992) and neuroimaging (e.g., Clark et al, 1996;Kanwisher, McDermott, & Chun, 1997;Sergent & Signoret, 1992) indicates the highly specialized nature in which faces are processed (Haxby, Hoffman, & Gobbini, 2000). Further attesting to their status as a special stimulus, evidence of attentional priority for faces has been observed across a range of behavioral paradigms, including visual search (e.g., Ro, Friggel, & Lavie, 2007), spatial cuing (e.g., Bindemann, Burton, Langton, Schweinberger, & Doherty, 2007;Theeuwes & Van der Stigchel, 2006), flicker (Ro, Russell, & Lavie, 2001;Weaver & Lauwereyns, 2011), go/no-go (e.g., Bindemann, Burton, Hooge, Jenkins, & de Haan, 2005), and inattentional blindness paradigms (e.g., Devue, Laloyaux, Feyers, Theeuwes, & Brédart, 2009;Mack & Rock, 1998).…”
mentioning
confidence: 99%
“…In support of this view, there is no strong evidence that information related to identity, race, or gender (which are partly dependent on mid and high spatial frequencies; Smith, Volna, & Ewing, 2016;Vuilleumier, Armony, Driver, & Dolan, 2003) specifically draws attention to the location of a face. Although it seems possible to identify faces with minimal levels of attention (Reddy, Reddy, & Koch, 2006), neither one's own face nor other personally familiar faces capture attention in a bottomup fashion (Devue & Brédart, 2008;Devue, Laloyaux, Feyers, Theeuwes, & Brédart, 2009;Keyes & Dlugokencka, 2014;Laarni, Koljonen, Kuistio, Kyrolainen, Lempiainen, & Lepisto, 2000;Qian, Gao, & Wang, 2015). While familiar faces can clearly bias attention, they do so by delaying disengagement once the face has been attended (Devue & Brédart, 2008;Devue, Van der Stigchel, Brédart, & Theeuwes, 2009;Keyes & Dlugokencka, 2014).…”
mentioning
confidence: 99%
“…We posit that plausible adaptive cognitive and neural mechanisms can account for oculomotor capture by faces as a class. Pre-attentive mechanisms that scan the environment to detect faces automatically ('t Hart, Abresch, & Einhäuser, 2011;Elder, Prince, Hou, Sizintsev, & Olevskiy, 2007;Lewis & Edmonds, 2003) may exist to compensate for the difficulty in distinguishing subtle facial characteristics at periphery or in unattended central locations (Devue, Laloyaux, et al, 2009). This could be achieved through magnocellular channels that extract low spatial frequencies that are used for holistic processing (Awasthi, Friedman, & Williams, 2011a, 2011bCalvo, Beltrán, & Fernández-Martín, 2014;Girard & Koenig-Robert, 2011;Goffaux, Hault, Michel, Vuong, & Rossion, 2005;Johnson, 2005;Taubert, Apthorp, Aagten-Murphy, & Alais, 2011).…”
mentioning
confidence: 99%